Validasi Marker Infeksi Dini Ganoderma pada Kelapa Sawit di Tiga Lokasi Endemik Ganoderma - Galuh Wening Permatasari; Mayumi Puspita; Irma Kresnawaty; Agustin Sri Mulyatni; Deden Dewantara Eris; Happy Widiastuti; Kuwat Triyana; Priyono Priyono (Jurnal Penelitian Kelapa Sawit, 2023)
A serious disease that affects the viability of the oil palm industry is basal stem rot, which is caused by Ganoderma. The current level of disease can be viewed as unmanageable, given that the palms were growing in an unfavorable or unsuitable climate. Today, there are numerous approaches to diagnose diseases early, and one of them using molecular methods. Seven genes for early infection markers were effectively generated by a reference's transcriptome study, including LEUCO, ETHYLENE, CHALCONE, ANTHOCYANIDIN, ETHYLENE, MANNOSE, and SENESCENCE. The purpose of this study is to validate and confirm the presence of Ganoderma infections in three endemic oil palm field in Indonesia i.e. Cisalak Baru, Rejosari, and Bekri plantation. This study conducted real time qPCR of RNA from oil palm roots with four different severities of infection. Manual processing of RNA isolation and cDNA synthesis were carried out, to provide quantification expression level. In addition, gene ontology (GO) analysis was also performed in order to explain the roles of each gene tested. The results revealed that CHALCONE is the only marker that consistently elucidate the Ganoderma's early infection appear in three locations. The drawbacks of the analysis results are tightly correlating to the age of oil palm as well as endemic location. GO results declare that seven genes function related to the response of infection. This work was successful in confirming early infection in three places, elucidating the variables influencing the efficacy and sensitivity of molecular detection, and revealing the function and importance of particular genes for detection.